Professional Development of Christian Education Teachers Based on Scientific Writing Products to Improve Learning Quality and Career Improvement Assisted Module - Junihot M. Simanjuntak; Heriyanto; Marinus Waruwu (Jurnal Pendidikan Indonesia, 2022)
Research and publication of scientific papers become the main problems in the professional development of teachers. This aims of this research is to develop sustainable professional teacher through research product-based training models and the publication of scientific papers. It analyses the need for a training management model that can increase the professionalism of Christian education subject teachers who are civil servants to produce scientific papers. This research is using qualitative methods with a Research and Development model approach. The data analysis technique used the Mann-Whitney U test technique. Sources of training data are primary data and secondary data. Primary data was obtained from the interview process of all training participants, and secondary data was obtained based on the analysis of the training module directory, training directory and examples of training product administrators. The results showed the validity level of the training module was in a good category (72%), the results of scientific papers using the IHT module are higher than before using the training module; the product of scientific papers produced by the teacher has met the requirements for promotion; the resulting training product in the form of scientific papers is useful for improving school performance and teacher motivation for higher careers.